Environmental movements in India - Karan, P P (Geographical Review. New York: Jan 1994. Vol. 84, Iss. 1; pg. 32, 1994)
Grassroots environmental movements following Gandhian nonviolent tradition are expanding in India. The Chipko movement in the Himalaya, Save the Narmada movement in central India and the Silent Valley movement in the Malabar region of southern India are discussed